The potential to change pacing and performance during 4000-m cycling time trials using hyperoxia and inspired gas-Content deception - Davies, M. J.; Clark, B.; Garvican-Lewis, L. A.; Welvaert, M.; Gore, C. J.; Thompson, K. G. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine if a series of trials with fraction of inspired oxygen (FiO2) content deception could improve 4000-m cycling time-trial (TT) performance. Methods: A total of 15 trained male cyclists (mean [SD] body mass 74.2 [8.0] kg, peak oxygen uptake 62 [6] mL/kg·min) completed six 4000-m cycling TTs in a semirandomized order. After a familiarization TT, cyclists were informed in 2 initial trials they were inspiring normoxic air (NORM, FiO2 0.21); however, in 1 trial (deception condition), they inspired hyperoxic air (NORM-DEC, FiO2 0.36). During 2 subsequent TTs, cyclists were informed they were inspiring hyperoxic air (HYPER, FiO2 0.36), but in 1 trial, normoxic air was inspired (HYPER-DEC). In the final TT (NORM-INFORM), the deception was revealed and cyclists were asked to reproduce their best TT performance while inspiring normoxic air. Results: Greater power output and faster performances occurred when cyclists inspired hyperoxic air in both truthful (HYPER) and deceptive (NORM-DEC) trials than NORM (P<.001). However, performance only improved in NORM-INFORM (377 W; 95% confidence interval [CI] 325-429) vs NORM (352 W; 95% CI 299-404; P<.001) when participants (n=4) completed the trials in the following order: NORM-DEC, NORM, HYPER-DEC, HYPER. Conclusions: Cycling performance improved with acute exposure to hyperoxia. Mechanisms for the improvement were likely physiological; however, improvement in a deception trial suggests an additional placebo effect. Finally, a particular sequence of oxygen deception trials may have built psychophysiological belief in cyclists such that performance improved in a subsequent normoxic trial.